Drug and alcohol abuse at the work-place - Ismail, Fadillah; Teh, Hui Chin; Ali Hassan Humaid Alhosani, Adnan; Lee, Te Chuan (Penerbit UTHM, 2020)
Malaysia is the country that have strong legal control to the drug and alcohol among the Asia countries. Malaysia has prepared the guidelines that intended to provide guidance to employers and employees to prevent and respond to the issues from drug and alcohol use which to satisfy their obligations under the OSHA 1994. This action is to develop the prevention responses to the drug and alcohol issues in the workplace within Malaysia. There are many of issues that occurred in the workplace because the various forms of drug and alcohol that use by employees that effect their job performance when they are on duty especially operating machines such as alcohol, illicit drugs (heroin), non-predicate medicines (cough medicine) and others. Besides that, drug and alcohol abuse at the workplace may cause the risk injury of employees. Therefore, drug and alcohol use are totally prohibited in Malaysia and totally should be prevented in the workplace that can result in issues at work.